Disney Magic through the Disney Guest Experience - Vergara, Raymond Allan; Vergara, Kimberly Christie S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study discusses how Disney delivers a unique and memorable guest experience. Through subjective personal introspection, it examines Disney's approach to co-creating a profound guest experience. The Disney guest experience is profound because it delivers an experience that touches on all six dimensions of an experience: sensorial, emotional, cognitive, pragmatic, lifestyle, and relational.